PENERAPAN KEBIJAKAN KAWASAN TANPA ROKOK DI KAMPUS UNIVERSITAS RIAU - Zul Arifin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is motivated by a number of students, faculty, and employees of the University of Riau in particular the Faculty of Social and Political Sciences, a lack of awareness of students on health, lack of awareness of smokers to stop smoking on No Smoking Area (KTR), and lack of policy No Smoking Area (KTR) made by the campus of the University of Riau. This study aims to: (1) understand, explain, and analyze the implementation of policies smoking area on the campus of the University of Riau; (2) determine what factors that affect the application of policies smoking area on the campus of the University of Riau; and (3) determine the factors that hinder the implementation of regional policy without a cigarette on the campus of the University of Riau. This research is a qualitative descriptive method. Data were obtained from interviews, and literature relevant to the research problem. Based on the research results: (1) the application of the policy of No Smoking Area (KTR) can be done by studying some aspects and following several stages of public policy, that policy is made not only limited to the adoption of policies, but also implemented and evaluated the extent of the impact; (2) the factors of policy implementation factors include communication, resources owned, tendencies or behavior-behavior of implementing policies, bureaucratic structures owned, may also consider factors measures and policy objectives, the sources policy, communication between the organization and implementation activities, the characteristics of the implementing agencies, economic conditions, social and political, as well as the tendency of the executive; and (3) factors inhibiting the adoption of a policy of covering the human factor, the passage of the policy, and the firmness of implementation. But to know the inhibiting factors of the implementation of a policy is by taking into account the contents of policies formulated, information obtained policymaker, a factor of support from policy makers and implementers, as well as the exact distribution of the potential in the field of implementing the policy.Keywords: Policy, No Smoking Area (KTR)